Penerapan Metode Praktik pada Pemain Keyboard dalam Mengiring Ibadah di Gereja Kibaid Dirgantara Makassar - Richard Kapoyos; Laura Megawaty Manalu; Musa Kiring (Institut Agama Kristen Negeri Manado, 2024)
The aim of this research is to determine the application of practical methods to keyboard players in accompanying worship services at church. The problem in this research is how to apply practical methods to keyboard players in accompanying worship in church. In this research, the author used a qualitative method approach. The qualitative method is data collection carried out personally, where the researcher plays an important role in this research to collect data or information related to this research. Results and discussion in this research The practical method is a method that is carried out by explaining while providing training material to the training participants. This method can be said to be good and appropriate in carrying out music training, especially keyboards. Applying this practical method can make it easier for trainees to understand the training material and can also practice it quickly and well. This method also allows teenagers to improve their musicality and improve their skills (psychomotor) in music.